The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1080/10599240903389599
|View full text |Cite
|
Sign up to set email alerts
|

Community Exposure Following a Drip-Application of Chloropicrin

Abstract: Ocular, respiratory, and systemic symptoms on the evening of October 5, 2005, corresponded to a plume of chloropicrin, with estimated concentrations as high as 0.15 ppm, in the community of Salinas, California. Cases occurred between 0.36 and 2.89 miles from the application site. Use of irritant agricultural fumigants near residential neighborhoods can produce a risk of illness for distances more than 2 miles from the site of application. Air modeling is useful for evaluating the relationship between possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
(16 reference statements)
1
8
0
Order By: Relevance
“…Studies in human volunteers indicate that lacrimation and blepharospasm is apparent at 5.0 mg min/m 3 , conjunctival irritation is apparent at 10-100 mg min/m 3 , and intolerable ocular irritation developed at 500 mg min/m 3 (Fries andWest, 1921, Prentiss andFisher, 1937). These studies are consistent with more recent findings following an industrial accident in California that produced a plume of chloropicrin with estimated air concentrations between 0.17-1.0 mg/m 3 (Barry et al, 2010). Of the 324 residents who reported symptoms consistent with chloropicrin exposure, 302 (93.2%) presented with ocular symptoms such as lacrimation, ocular pain and burning.…”
Section: Choking Agentssupporting
confidence: 91%
“…Studies in human volunteers indicate that lacrimation and blepharospasm is apparent at 5.0 mg min/m 3 , conjunctival irritation is apparent at 10-100 mg min/m 3 , and intolerable ocular irritation developed at 500 mg min/m 3 (Fries andWest, 1921, Prentiss andFisher, 1937). These studies are consistent with more recent findings following an industrial accident in California that produced a plume of chloropicrin with estimated air concentrations between 0.17-1.0 mg/m 3 (Barry et al, 2010). Of the 324 residents who reported symptoms consistent with chloropicrin exposure, 302 (93.2%) presented with ocular symptoms such as lacrimation, ocular pain and burning.…”
Section: Choking Agentssupporting
confidence: 91%
“…Chloropicrin, also known as trichloronitromethane and nitrochloroform, is a halogenated fumigant that reacts with the amino acids that form the protein structure of different pests (Albritton et al, 1998;Barry et al, 2010). It has been steadily used in California since 1991.…”
Section: Chloropicrinmentioning
confidence: 99%
“…It has been steadily used in California since 1991. Barry et al (2010) reported that residuals of chloropicrin used in irrigation lines for post-application water treatment have contributed to considerable health problems in local communities. Barry et al (2010) reported that residuals of chloropicrin used in irrigation lines for post-application water treatment have contributed to considerable health problems in local communities.…”
Section: Chloropicrinmentioning
confidence: 99%
“…Increased respiratory symptoms have been reported as a result of community exposure to chloropicrin following application (Barry et al 2010; CDC 2004). A larger analysis of chloropicrin-related illness in California from 1992–2003 found that 54% of cases involved respiratory irritation (Oriel et al 2009).…”
Section: Introductionmentioning
confidence: 99%